2000
DOI: 10.1099/0022-1317-81-1-151
|View full text |Cite
|
Sign up to set email alerts
|

Complete genomic RNA sequence of western equine encephalitis virus and expression of the structural genes

Abstract: The complete nucleotide sequence of the 71V-1658 strain of western equine encephalitis virus (WEE) was determined (minus 25 nucleotides from the 5h end). A 5h RACE reaction was used to sequence the 5h terminus from WEE strain CBA87. The deduced WEE genome was 11 508 nucleotides in length, excluding the 5h cap nucleotide and 3h poly(A) tail. The nucleotide composition was 28 % A, 25 % C, 25 % G and 22 % U. Comparison with partial WEE sequences of strain 5614 (nsP2-nsP3 of the nonstructural region) and strain BF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Three of the major changes in E2 were clustered within a 68 aa stretch and could possibly play an important role in the efficiency with which WEEV binds/enters host cells. Previous studies have shown that the secondary structure of the stem-loops in the 59 NTR of other alphavirus genomes plays a role in virus neurovirulence (Evans et al, 1985;Kinney et al, 1993;Logue et al, 2008;Netolitzky et al, 2000). The single nucleotide difference between MCM and IMP at position 34, however, did not affect the secondary structure of the sole stem-loop of the WEEV 59 NTR.…”
Section: Discussionmentioning
confidence: 79%
“…Three of the major changes in E2 were clustered within a 68 aa stretch and could possibly play an important role in the efficiency with which WEEV binds/enters host cells. Previous studies have shown that the secondary structure of the stem-loops in the 59 NTR of other alphavirus genomes plays a role in virus neurovirulence (Evans et al, 1985;Kinney et al, 1993;Logue et al, 2008;Netolitzky et al, 2000). The single nucleotide difference between MCM and IMP at position 34, however, did not affect the secondary structure of the sole stem-loop of the WEEV 59 NTR.…”
Section: Discussionmentioning
confidence: 79%
“…We purposefully chose this protein antigen for our LANAC formulation for several reasons. First, although E2 protein is the major neutralizing antigen, E1 is highly conserved among distinct alphaviral species (9,10), and antibody to E1 is protective (11). Second, the E1 of WEEV is a recent ancestor of the E1 from a Sindbis-like virus, which has been shown to induce cross-reactive and cross-protective antibodies (11,35).…”
Section: Discussionmentioning
confidence: 99%
“…Subunit vaccines consisting of recombinant forms of WEEV E2 or E1 have been reported to induce significant protection in animal models (6)(7)(8). Although E2 is the major neutralizing antigen, E1 is highly conserved among alphaviruses (9,10). Thus, E1 is an excellent vaccine candidate because it might offer broader ("pan-alphavirus") protection against fatal encephalitis.…”
mentioning
confidence: 99%
“…The latter authors postulate that bats may become infected, especially during epizootics in other hosts. The prototype virus of the genus Alphavirus is the Sindbis virus (SINV), which belongs together with the Highland J, Fort Morgan, Buggy Creek and Aura virus to the Western equine encephalomyelitis antigenic complex (HubĂĄlek 2008;Lundström and Pfeffer 2010;Netolitzky et al 2000). It was first recognized and isolated from Culex pipiens and Cx.…”
Section: Togaviridaementioning
confidence: 99%